2021
DOI: 10.1186/s12891-021-04652-4
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal symptoms and their associated risk factors among Saudi office workers: a cross-sectional study

Abstract: Background Musculoskeletal disorders are common worldwide. Several factors are suggested in their aetiology, one of which is ergonomics alongside other individual factors. This study aims at investigating the prevalence of musculoskeletal disorders among administrative office workers at a large university in Saudi Arabia. Methods This cross-sectional study recruited office workers at a Saudi university. A questionnaire was used that involved three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
3
10
2
5
Order By: Relevance
“…The study found that years of experience had a significant impact on the prevalence of musculoskeletal symptoms; the musculoskeletal symptoms increased in radiologists with more years of experience. This finding is consistent with the findings of Alomar et al, who reported that MSS were positively correlated with years of experience [ 33 ]. In addition, as work experience increases, chronic MSS may lead to cumulative tension in muscles and tendons, decreasing blood supply to the corresponding areas.…”
Section: Discussionsupporting
confidence: 93%
“…The study found that years of experience had a significant impact on the prevalence of musculoskeletal symptoms; the musculoskeletal symptoms increased in radiologists with more years of experience. This finding is consistent with the findings of Alomar et al, who reported that MSS were positively correlated with years of experience [ 33 ]. In addition, as work experience increases, chronic MSS may lead to cumulative tension in muscles and tendons, decreasing blood supply to the corresponding areas.…”
Section: Discussionsupporting
confidence: 93%
“…We found that years of experience had a signi cant impact on the prevalence of musculoskeletal symptoms; the musculoskeletal symptoms increased in radiologists with more years of experience. This nding is consistent with the ndings of Alomar et al, who reported that MSS were positively correlated with years of experience [29]. In addition, as work experience increases, chronic musculoskeletal symptoms may lead to cumulative tension in muscles and tendons, decreasing blood supply to the corresponding areas.…”
Section: Discussionsupporting
confidence: 91%
“…Helmina, Diani and Hafifah (2019) revealed that nurses aged > 35 years experienced more severe complaints of MSDs, and the statistical analysis results showed that there is a relationship between age and the condition. Similar results were obtained in a study on office workers at universities in Saudi Arabia, where people >38 years had disabilities associated with the disorders (AlOmar et al, 2021).…”
Section: Agesupporting
confidence: 86%
“…Aulia, Ginanjar and Fathimah (2019) stated that there is a significant relationship between exercise habits and MSDs, where people with low habits are 3.4 times more at risk of MSDs. Physical exercise in the workplace as well as the provision of ergonomic facilities is an effective combined action in occupational health and safety to prevent musculoskeletal symptoms (AlOmar et al, 2021).…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation